Literature review of spontaneous subarachnoid haemorrhage: risk factors, diagnostic features, and complications (Part I) - Grigaitė , J.; Rutkauskaitė, G.; Piliponis , L.; Ščerbak , J.; Jatužis, D.; Valaikienė, J. (Neurologijos seminarai, 2021)
Ruptured cerebral aneurysm-induced subarachnoid haemorrhage (SAH) is a common cause of disability and death in middle-aged people. SAH is more common in females than males, among non-white ethnicity, and is most commonly diagnosed in Finland and Japan. Familial predisposition to SAH and/or aneurysms significantly increases the risk of the disease. Among the adjustable risk factors, smoking, arterial hypertension, and alcohol abuse have the most significant effects. PHASES and other scales covering the most important influencing factors have been introduced into clinical practice to assess the risk of aneurysm rupture. The most significant clinical sign of SAH is a sudden and severe headache, also known as a thunderclap headache. Impaired consciousness, convulsions, cranial nerve damage, paresis/plegia, and meningeal symptoms may also be observed. Computed tomography (CT) and/or lumbar puncture are the main instrumental studies supporting the diagnosis of SAH, while digital subtraction angiography is considered the gold standard in the diagnosis of intracranial aneurysms. More and more diagnostic tools are being introduced into clinical practice to rule out SAH, such as magnetic resonance imaging with GRE, SWI, FLAIR sequences, which exceed the sensitivity and specificity of CT, especially in the first days of bleeding. Mortality is significantly increased by common local and systemic complications: recurrent bleeding, hydrocephalus, acute convulsions, cardiovascular complications, and cerebral ischemia, the most common cause of which is vasospasm.
Keywords: subarachnoid haemorrhage; ntracranial aneurysm; thunderclap headache; risk factors; diagnostics